3. Similarities Across the Centuries: A Comparison Between Two Vocal Works by Barbara Strozzi and Peter Maxwell Davies - Marisi Rossella (Sciendo, 2018)
Musical creativity may be expressed by composers in diverse ways: sometimes they compose fully original works, which are characterized by specific features making them unique. Other times, musicians may feel a particular affinity with colleagues who lived centuries before, or identify peculiar resemblances between the time they live in, and a previous epoch, such as similar cultural climate and approach to life: in these cases, composers may author pieces which show surprising similarities with those of some predecessors. The present study compares a work of the seventeenth century, composed by Barbara Strozzi, and one composed in the 1960s by Peter Maxwell Davies, highlighting their similarities.